Sistem Informasi Akademik berbasis Client Server pada SMP Negeri 2 Delanggu Klaten - Sri Siswanti, Dwi Agung Nugroho Sulistyo, Didik Nugroho (Jurnal Ilmiah SINUS, 2013)
The purpose of this paper to find academic information system in SMP Negeri Delanggu Klaten and improve the system for more effetive and efficient and also shows how the processing of data entry and reports of academic data, so it is expected to expedite the processing of academic data. The Metode use was observation techniques, interview techniques carried out directly on the research by collecting information through the media of books as library material. And sourcesof data drawn form the activities carried out in the library (Primary Data Source), these data are taken from reverensi associated with the library (Secondary Data Source). In completing these authora use a computer as a tool to generate more Â accurate results, relevant and valid. At the same time produce useful information and can be completed more quickly in line with expectations. Â The application program used is Borland Delphi 7.0 application program as tool for human as user should and can facilitate in making the statement in the program â€œAcademic Information System based Client Keywords: Academic Information System Client Server